2014
DOI: 10.1371/journal.pone.0113107
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Esculentoside A on Experimental Acute Liver Injury in Mice

Abstract: Inflammatory response and oxidative stress are considered to play an important role in the development of acute liver injury induced by carbon tetrachloride (CCl4) and galactosamine (GalN)/lipopolysaccharides (LPS). Esculentoside A (EsA), isolated from the Chinese herb phytolacca esculenta, has the effect of modulating immune response, cell proliferation and apoptosis as well as anti-inflammatory effects. The present study is to evaluate the protective effect of EsA on CCl4 and GalN/LPS-induced acute liver inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…9) Several studies have shown how some compounds show protective effects against CCl 4 -induced hepatotoxicity. [7][8][9][10] Some of these compounds attenuated oxidative stress and the inflammatory response. 10) As JTX modulates the immune system, such as Toll-like receptor 4 signaling pathways, 25,26) it might also suppress the inflammatory response activated by CCl 4 .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…9) Several studies have shown how some compounds show protective effects against CCl 4 -induced hepatotoxicity. [7][8][9][10] Some of these compounds attenuated oxidative stress and the inflammatory response. 10) As JTX modulates the immune system, such as Toll-like receptor 4 signaling pathways, 25,26) it might also suppress the inflammatory response activated by CCl 4 .…”
Section: +mentioning
confidence: 99%
“…In addition, associated protective mechanisms possibly act on each of the five steps. [7][8][9][10] The Japanese herbal medicine "Juzen-taiho-to" (JTX) is a Kampo medicinal prescription, and has been used historically in Japan for the treatment of cancers, rheumatoid arthritis, and atopic dermatitis. 11) JTX is consisting of ten medicinal herbs in the indicated amounts (g per day in human intake);…”
mentioning
confidence: 99%
“…Several studies have shown some compounds show protective effects against CCl 4 -induced hepatotoxicity (Singh et al, 2008;Huang et al, 2012;Ma et al, 2014;Zhang et al, 2014). These investigations focused primarily on blood levels of liver enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (markers of liver damage), histological evaluation, lipid peroxidation, and expression levels of cytochromes P450.…”
Section: Introductionmentioning
confidence: 99%
“…Through these steps, necrosis is induced; this induction is termed as the fifth step. Multiple compounds have been reported to show protective effects against CCl 4 -induced hepatotoxicity, and associated protective mechanisms have been proposed to act on each of the five steps [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%